A experiência do microcrédito e o modelo das sociedades de crédito ao microempreendedor (SCM) - Oliveira Neto, José Pires de (2007)
This work is a study about the current model performance of the Micro Entrepreneur Societies ( SCM ). Particularly, it is shown the civil mark development of these institutions, their performance limits and difficulties found for the full development of this private category of microcredit institution that act in many of Brazilian states. Up to that it is explored the dilemma between their social goals, the assistance to microentrepreneurs without access to the formal financial system, and your economic goals, the partners capital remuneration of these companies. For so much, the work is broken in three chapters, besides the introduction and of the final conclusion. The first chapter boards the reason why and as arose microcredit institutions in connection with particularities in the public’s target assistance in this market. Second chapter exposes which ones are the principles that govern microcredit entities performance and which ones are the difficulties and solutions found with the experience and evolution of those. In the third chapter are analyzed SCMs specifically. In the study It is introduced the current civil mark, it is done a economic and financial analysis of this companies and a comparative with other juridical entities models that act in microfinances Brazilian marked. Yet, statistics tests conclude that the SCMs are in a economic environment that not allows their sustainability and growth. Finally, it is suggested some changes so that has larger growth opportunities and SCMs development.